A large‐scale phylogeny of the lycophyte genus Selaginella (Selaginellaceae: Lycopodiopsida) based on plastid and nuclear loci. (24th August 2015) - Zhou, Xin‐Mao; Rothfels, Carl J.; Zhang, Liang; He, Zhao‐Rong; Le Péchon, Timothée; He, Hai; Lu, Ngan Thi; Knapp, Ralf; Lorence, David; He, Xing‐Jin; Gao, Xin‐Fen; Zhang, Li‐Bing
Abstract: The lycophyte genus Selaginella alone constitutes the family Selaginellaceae, the largest of the lycophyte families. The genus is estimated to contain 700–800 species distributed on all continents except Antarctica, with highest species diversity in tropical and subtropical regions. The monophyly of Selaginella in this broad sense has rarely been doubted, whereas its intrageneric classification has been notoriously contentious. Previous molecular studies were based on very sparse sampling of Selaginella (up to 62 species) and often used DNA sequence data from one genome. In the present study, DNA sequences of one plastid ( rbcL ) and one nuclear (ITS) locus from 394 accessions representing approximately 200 species of Selaginella worldwide were used to infer a phylogeny using maximum likelihood, Bayesian inference and maximum parsimony methods. The study identifies strongly supported major clades and well resolves relationships among them. Major results include: (i) six deep‐level clades are discovered representing the deep splits of Selaginella ; and (ii) 20 major clades representing 20 major evolutionary lineages are identified, which differ from one another in molecular, macro‐morphological, ecological and spore features, and/or geographical distribution.